Validitas LKPD Elektronik Berbasis PBL Untuk Meningkatkan Keterampilan Metakognitif Peserta Didik Pada Materi Asam Basa - Ainun Tazkia; Rusly Hidayah (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2023)
This study aims to determine the validity of e-worksheets based on PBL (Problem-Based Learning) to improve students' metacognitive skills in acid-base material. The 4D model development implemented in this study has four stages, namely Define, Design, Develop, and Disseminate, which is limited to the Develop stage. The validators comprised two chemistry lecturers at Surabaya State University and a chemistry teacher from a senior high school in Gresik. The validation sheet is a research instrument used to assess the content and construct criteria of e-worksheets. The results of the three electronic LKPD validations developed on the content and construct criteria obtained percentages of 91.67% and 95.63% which were included in the very valid criteria